Strategi Pemasaran Fintech Syariah dalam Meningkatkan Adopsi Layanan Keuangan Digital di Indonesia - Abustan Nur; Amanda Julianti; Nurul Waqia; Eki Pratiwi; Akbar M.Sunusi; Rika Rika (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study analyzes Islamic fintech marketing strategies in increasing the adoption of digital financial services in Indonesia. The rapid growth of financial technology has encouraged Islamic fintech institutions to design marketing strategies that are not only technology-driven but also aligned with sharia principles. This study employs a qualitative approach using a literature review method by examining national journals, reputable international journals, and academic books related to Islamic fintech, digital marketing, financial literacy, consumer trust, and sharia compliance. The findings indicate that Islamic fintech marketing strategies significantly influence consumer adoption through digital marketing optimization, financial literacy education, brand trust, integration of sharia values, and transparency of digital contracts (akad). Transparency in sharia-based digital transactions strengthens consumer confidence and differentiates Islamic fintech from conventional financial services. In addition, the use of educational content, personalized communication, and accessible digital platforms can enhance public understanding of Islamic financial products. Therefore, effective, transparent, and sharia-compliant marketing strategies are essential for accelerating the adoption and sustainability of Islamic digital financial services in Indonesia.